2019
DOI: 10.1016/j.apenergy.2019.113615
|View full text |Cite
|
Sign up to set email alerts
|

An improved Thevenin model of lithium-ion battery with high accuracy for electric vehicles

Abstract: This paper proposes an improved Thevenin model of the Lithium-ion battery taking into account temperature influence on the calculation accuracy of the open circuit voltage of a battery. The calculation accuracy of the terminal voltage of a battery is improved without increasing the order of the model. Firstly, the model was proposed based on Thevenin model and the relationship between the open-circuit voltage and the state of charge. Then, based on the experimental results of the open-circuit voltage test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The main parameters of the test microgrid are shown in Table 2, and the structure of the proposed strategy in MATLAB/Simulink 2018b is shown in Figure 10. The important simulation setups include: (1) the control period is 5e −6 s; (2) the power disturbances can be imposed on the system by adding or reducing the load units; (3) the distributed generation systems are equivalent to a DC voltage source [41].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The main parameters of the test microgrid are shown in Table 2, and the structure of the proposed strategy in MATLAB/Simulink 2018b is shown in Figure 10. The important simulation setups include: (1) the control period is 5e −6 s; (2) the power disturbances can be imposed on the system by adding or reducing the load units; (3) the distributed generation systems are equivalent to a DC voltage source [41].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The equivalent circuit model is widely used in battery management systems to describe the dynamics of the battery due to its clear physical meaning and balance between computational accuracy and complexity [6,7,21]. Over the past decade, researchers have proposed many kinds of equivalent circuit models, such as the Rint model [22], Thevenin model [23], PNGV model [24], and GNL model [25]. Comparing the SOC estimation accuracy and robustness of the above different equivalent circuit models, Lai, Zheng and Sun [9] and Hu, et al [26] found that the estimation accuracy does not always improve with the increase of the capacitive resistance network.…”
Section: Lithium-ion Battery Modelingmentioning
confidence: 99%
“…The first-order Thevenin circuit is adopted as the battery model, in which a RC link that can describe the polarization of the battery is added to the Rint model consisting of only one constant voltage source and one resistor [36]. Compared with the more accurate PNGV model and Massimo Ceraolo model, it reduces the difficulty of parameter identification and accurately simulates the dynamic characteristics of the battery [37].…”
Section: Actuator Mathematical Modelingmentioning
confidence: 99%